(untitled) (Comprehensive Journal of Science, 2025)
Objective: This study aims to monitor and analyze the environmental impacts resulting from random urban sprawl on vegetation cover in the suburbs of Al-Zawiya City (Juda’im, Al-Harsha, Abu Sarah, and Al-Matrad). Methodology: The study adopted an integrated methodology combining theoretical analysis with modern technical applications, including: Analysis of satellite imagery (Landsat) for 2000 and 2024. Application of the Normalized Difference Vegetation Index (NDVI) to measure vegetation density. Use of Change Detection techniques to track spatial transformations. Integration of Geographic Information Systems (GIS) and Remote Sensing. Key Findings: Severe Vegetation Degradation: The area lost approximately 51% of its vegetation cover over a quarter-century, with green spaces declining from 65% in 2000 to 32% in 2024. Random Growth Pattern: Prevalence of Ribbon Development along main road axes, leading to fragmentation of green infrastructure. Agricultural Land Fragmentation: Large agricultural holdings transformed into unregulated small residential plots. Serious Environmental Consequences: Exacerbation of Urban Heat Island effect, soil degradation, disruption of hydrological cycles, and loss of biodiversity. Recommendations: Implement smart surveillance using geospatial technologies. Update structural plans to incorporate green belts. Enact strict legislation to protect agricultural lands. Develop integrated planning strategies for urban sustainability.